Efficacy of Instructional Module for Caregivers on Recovery of Traumatic Brain Injury (TBI) Patients - Kirti Verma; Shruti; Manoj Kumar Tewari; Sukhpal Kaur; Sandhya Ghai (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter aims to test the efficacy of instructional module for caregivers on recovery of TBI patients. Traumatic brain injury (TBI) is a silent public health epidemic and a major cause of disability, morbidity, and mortality worldwide. It is characterized by a breakdown in the normal function of the brain caused by collision, blow, and jolt to the head-neck-spinal cord, possibly leading to temporary or permanent impairment. The study was performed at the Neuro-Surgery Department of Post Gradu- ate Institute of Medical Education and Research (PGIMER), Chandigarh, India. A total of 82 patients with 41 each in experimental and control groups and their caregivers were included in the study. The effectiveness of the intervention was evaluated based on the frequency of deep vein thrombosis, deep chest infection, eye infection, bedsores, wound infection, constipation, urinary tract infection, and length of stay in both groups. Fever, constipation, and length of stay dramatically decreased in the experimental group. In the experimental group, lower rates of chest infections, bedsores developing, wound infections, and urinary tract infections were also seen. This study was performed to teach the caregivers using demonstrations and an instructional module. It aimed at facilitating caregivers to perform the routine procedures regarding care of dependent head injury survivors.